A rare case report of Langerhans cell histiocytosis exclusive to the colon in adults - Martins, Daniela; Tenreiro, Nádia; Cubal, Francisco; Dupont, Margarida; Costa, Pedro; Pinto-de-Sousa, João (International Surgery Journal, 2024)
Langerhans cell histiocytosis (LCH) is a rare disease characterized by abnormal proliferation of atypical Langerhans cells, predominantly affecting children. Adult-onset LCH is even rarer and typically involves the lungs, bones, and skin. There is a shortage of knowledge regarding various aspects related to its origin, evolution, and treatment. We present a case of a 63-year-old female with an exceptional manifestation of single-organ LCH in the colon, discovered incidentally during routine colorectal cancer screening. The patient’s past medical history included a right colectomy for an ileal neuroendocrine tumor with hepatic metastasis. A comprehensive diagnostic workup revealed a BRAF V600E mutation in LCH tumor cells. The patient did not receive any systemic therapy and remains asymptomatic at the 9-month mark post-diagnosis. This case underscores the complexity of LCH diagnosis and the need for multidisciplinary management.